Erratum : Meningkatkan Kepemimpinan dan Kerja Sama melalui Outdoor Education Camping Program - Rafdlal Saeful Bakhri; Arfin Deri Listiandi; Moh. Nanang Himawan Kusuma; Didik Rilastiyo Budi; Topo Suhartoyo; Rohman Hidayat (STKIP Muhammadiyah Kuningan, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v5i1.704 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.